Mutu Pesantren Salafiyah dalam Konteks Penyelenggaraan Pendidikan Nasional - Khoirul Anam (Ta'allum: Jurnal Pendidikan Islam, 2014)
Islamic boarding school contribute significantly to the establishment of national education specifically in the following matters, namely, (1) internalization of norm, (2) wisdom, (3) good behavior/akhlaq al karimah, (4) good morality. In other words, Islamic boarding school affects the way of life in Indonesia. In the context of improving the quality and access toward education, the role of Islamic boarding school must be elevated so that it can develop well as to respond the global era. This is so doing for a purpose of improving the quality of human resource in Indonesia.